THE EFFECT OF AIR POLLUTION ON CHRONIC OBSTRUCTIVE PULMONARY DISEASE EXACERBATIONS - Javorac, Jovan; Jevtic, Marija; Zivanovic, Dejan; Ilic, Miroslav (HEALTH CARE, 2021)
Chronic obstructive pulmonary disease (COPD) is one of the greatest global public health challenges, emerging as the third leading cause of death by 2030. Acute exacerbations of COPD (AECOPD) contribute to the accelerated deterioration of lung function, reduced quality of life and higher hospitalizations and mortality rates. The cause of exacerbation is usually an infectious agent, but the impact of exposure to environmental factors is being studied more thoroughly. Among them, atmospheric pollutants emerged as the most important ones. Multiple studies showed that elevated concentrations of particulate matter (PM), sulphur dioxide (SO2), nitric dioxide (NO2) and ozone (O3) in the atmosphere, have the most significant negative effect on patients with COPD, increasing hospitalisations and mortality rates due to COPD. While examining their effect on AECOPD, it is important to consider the mutual interactions of different air pollutants, as well as interactions with meteorological factors. In order to decrease the burden of COPD, it is necessary to implement all strategies that will reduce the incidence of COPD, including global reduction of air pollution. That will require the support of the world's most developed economies, a significant renewal of the necessary resources and, finally, radical social change.
Keywords: air pollution, chronic obstructive pulmonary disease, exacerbation, particulate matter, sulphur dioxide, nitric dioxide, ozone